Postoperative cognitive dysfunction – is it a problem for the anesthesiologist-intensivist? - Y. S. Aleksandrovich; T. I. Akimenko; K. V. Pshenisnov (Вестник анестезиологии и реаниматологии)
Postoperative cognitive dysfunction is a cognitive impairment developing in the postoperative period and confirmed by the data of neuropsychological testing. The article presents the results of a survey among practicing anesthesiologists-resuscitators in the Russian Federation on the problem of postoperative cognitive dysfunction. Methods. From January 21, 2019 to April 26, 2019, the survey was conducted among practicing anesthesiology and resuscitation physicians from 20 different regions of the Russian Federation, both in the online format and on paper. 340 questionnaires were analyzed, including 11 questions about the problem of cognitive impairment in the postoperative period. Microsoft Excel, Survio, Statistica 8.0 were used for statistical processing of the results.Results. It was revealed that 74.7% of respondents were aware of the problem of postoperative cognitive impairment. At the same time, doctors ranked second in terms of the frequency of clinical manifestations, symptoms that were more characteristic of postoperative delirium. 18.5% had difficulty in describing the clinical manifestations of postoperative cognitive disorders. Analysis of the answers on the diagnosis of postoperative cognitive dysfunction showed that 45.3% of specialists considered neuropsychological testing mandatory in all patients undergoing surgery, 40% noted the need for mandatory testing of the cognitive functions in patients at risk, but 37.6% of doctors were not able to name a single method, and 34% answered that doctors of other specialties were engaged in neuropsychological testing. The survey results also showed the absence of a single treatment strategy for cognitive dysfunction.Сonclusions. The analysis of respondents' answers revealed insufficient awareness of specialists about clinical manifestations, diagnosis and treatment of postoperative cognitive dysfunction.